Impact of Brahman genetics on skin histology characteristics with implications for heat tolerance in cattle - Mateescu, Raluca G.; Sarlo Davila, Kaitlyn M.; Hernandez, Aakilah S.; Andrade, Andrea Nunez; Zayas, Gabriel A.; Rodriguez, Eduardo E.; Dikmen, Serdal; Oltenacu, Pascal A. (Frontiers in Genetics, 2023)
Cattle lose heat predominantly through cutaneous evaporation at the skin-hair coat interface when experiencing heat stress. Sweating ability, sweat gland properties, and hair coat properties are a few of the many variables determining the efficacy of evaporative cooling. Sweating is a significant heat dissipation mechanism responsible for 85% of body heat loss when temperatures rise above 86⁰F. The purpose of this study was to characterize skin morphological parameters in Angus, Brahman, and their crossbred cattle. Skin samples were taken during the summer of 2017 and 2018 from a total of 319 heifers from six breed groups ranging from 100% Angus to 100% Brahman. Epidermis thickness decreased as the percentage of Brahman genetics increased where the 100% Angus group had a significantly thicker epidermis compared to the 100% Brahman animals. A more extended epidermis layer was identified in Brahman animals due to more pronounced undulations in this skin layer. Breed groups with 75% and 100% Brahman genes were similar and had the largest sweat gland area, indicative of superior resilience to heat stress, compared to breed groups with 50% or lower Brahman genetics. There was a significant linear breed group effect on sweat gland area indicating an increase of 862.0 µm2 for every 25% increase in Brahman genetics. Sweat gland length increased as the Brahman percentage increased, while the sweat gland depth showed an opposite trend, decreasing from 100% Angus to 100% Brahman. The number of sebaceous glands was highest in 100% Brahman animals which had about 1.77 more sebaceous glands (P < 0.05) per 4.6 mm2area. Conversely, the sebaceous gland area was greatest in the 100% Angus group. This study identified significant differences in skin properties related to heat exchange ability between Brahman and Angus cattle. Equally important, these differences are also accompanied by significant levels of variation within each breed, which is indicative that selection for these skin traits would improve the heat exchange ability in beef cattle. Further, selecting beef cattle for these skin traits would lead to increased resilience to heat stress without disrupting production traits.